Sulfur Removal in Gasoil Feedstocks by Hydrotreating Process: A Comparative Study - Hussein, Sattar Jalil (Journal of Petroleum Research and Studies, 2024)
This study focuses on the hydrodesulfurization process of two different types of feedstocks: low and high-sulfur-content gasoil. The objective is to remove sulfur using a commercial Co-Mo/γ-Al2O3 catalyst obtained from the Daura refinery. The catalyst underwent various characterization tests, including BET surface area, crush strength, and composition tests using atomic absorption. Similarly, the feedstocks were also characterized before the evaluation process. The study explored the impact of temperature, LHSV (Liquid Hourly Space Velocity), and pressure as operating conditions for gasoil hydrodesulfurization (HDS) using the commercial catalyst Co-Mo/γ-Al2O3 in a pilot hydrotreating unit located at the petroleum research & development centre. The findings indicated that decreasing LHSV led to an increase in sulfur removal. Furthermore, increasing the temperature showed a general trend of increased sulfur removal for both high and low sulfur gasoil feedstocks. These trends were observed within the optimal operating conditions of LHSV 1 hr-1, 375oC temperature, 35 bar pressure, and a ratio of 200 cm3 of hydrogen gas to 200 cm3 of hydrocarbon. These results shed new light on the potential of this catalyst for effectively treating heavier fuels containing complex sulfur compounds.